2003
DOI: 10.1210/en.2003-0128
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression, Secretion, and Autocrine Action of C-Type Natriuretic Peptide in Cultured Adult Rat Cardiac Fibroblasts

Abstract: C-type natriuretic peptide (CNP), the third member of the natriuretic peptide family, is known to be synthesized in the central nervous system and vascular endothelial cells, in contrast to atrial natriuretic peptide and brain natriuretic peptide. However, there have been no studies concerning CNP production in cultured cardiac cells. Here, we examined the production and the local effect of CNP in cultured ventricular cells. Under serum-free conditions, adult rat cardiac fibroblasts secreted immunoreactive CNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
146
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(152 citation statements)
references
References 28 publications
5
146
0
1
Order By: Relevance
“…Furthermore, that the CNP/NPRB axis is responsible for the cardiac CNP effects is also supported by cell-based studies. CNP modulates the growth, proliferation, and hypertrophy of smooth muscle cells, cardiomyocytes and fibroblasts [31][32][33], and cGMP is implicated in all of these studies when CNP binds to its receptor NPRB. Additionally, our data on increased cGMP in the hearts of CNP-transgenic mice is congruent with findings in isolated rat and rabbit cardiomyocytes generating cGMP after CNP stimulation [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, that the CNP/NPRB axis is responsible for the cardiac CNP effects is also supported by cell-based studies. CNP modulates the growth, proliferation, and hypertrophy of smooth muscle cells, cardiomyocytes and fibroblasts [31][32][33], and cGMP is implicated in all of these studies when CNP binds to its receptor NPRB. Additionally, our data on increased cGMP in the hearts of CNP-transgenic mice is congruent with findings in isolated rat and rabbit cardiomyocytes generating cGMP after CNP stimulation [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CNP infusion markedly inhibited Ki-67-positive cells in fibrotic lesions of the lung. An in vitro study showed that CNP directly inhibited proliferation of cardiac fibroblasts through a guanylate cyclase-B-mediated cGMP-dependent pathway (7). Thus it is possible that the reduction of pulmonary fibrosis by CNP infusion may be mediated by a direct antiproliferative effect of CNP on fibroblasts in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CNP has been shown to suppress inflammation through inhibition of macrophage infiltration in injured carotid arteries of rabbits (20). Interestingly, CNP has been shown to directly inhibit cardiac fibroblast proliferation through a guanylate cyclase-B-mediated cGMP-dependent pathway (7). These findings suggest that CNP plays an important role in regulation of the cardiovascular system.…”
mentioning
confidence: 95%
“…Furthermore, transgenic overexpression of CNP in cardiomyocytes has been shown to prevent development of LV hypertrophy post‐MI 89. The cGMP‐dependent signaling appears to be central for antifibrotic effects of CNP 88, 90. Evidence from Burnett's laboratory suggests that a non‐cGMP‐dependent pathway also mediates the antifibrotic effects of CNP 78.…”
Section: Cnp In the Diseased Heartmentioning
confidence: 99%